An Empirical Insight into the Financial Globalization–Growth Nexus via Trade Openness: Evidence from Select South Asian Countries. Issue 2 (April 2023) - Sahoo, Malayaranjan; Sethi, Narayan
This article explores the relationship among financial globalization, trade openness and economic growth for the select South Asian countries, that is, Bangladesh, Bhutan, India, Pakistan and Sri Lanka over the time period 1990–2017. We have applied panel unit root test like that of Im–Pesaran–Shin (IPS) and Levin–Lin–Chu (LLC) to check the stationarity of the variables. Kao, Fisher and Pedroni's residual cointegration test has been considered to find out the long-run relationship among the variables. The cointegration results confirm that there exists a long-run relationship among the considered variables. The pairwise Granger Causality test confirms that there is a unidirectional causal relationship between growth and financial globalization, growth and foreign direct investment (FDI) and trade openness and financial globalization. Further, full modified ordinary least square (FMOLS) and dynamic ordinary least squares (DOLS) methods are used to find out the long-run dynamic relation between the variables, and the results show that financial globalization and trade openness have a positive and significant influence on economic growth. Our empirical findings suggest that South Asian countries should ensure that necessary policies require to be implemented if they need to partake in the gains from trade openness and capital flows, which would lead to stimulate the economic performance of the country. Also, governments should focus more on the enhancement of domestic financial system. In addition, an open economy requires global coordination to build a strong international financial system to prevent and manage financial crises or potential shock.